1990
DOI: 10.1346/ccmn.1990.0380511
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Phase Formation During Nuclear Waste-Glass Dissolution

Abstract: Abstract--Secondary minerals formed during simulated weathering of nuclear waste #asses have been identified by analytical electron microscopy. A complete description of the reacted #ass, from the outermost surface in direct contact with the leachant solution to the reacting front that migrates into the bulk #ass, was obtained. Manganese and iron oxyhydroxide phases and saponite were found to have precipitated onto the residual #ass surface from the leachant solution. Iron-bearing smectite, serpentine, and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 18 publications
(13 reference statements)
5
40
0
Order By: Relevance
“…However, the thinness of the layers formed at 50 and 100 n-I may have prevented resolution of similar sublayers. The alteration phases observed on the sample reacted for 100 days at 10 rn-1 are consistent with those formed on SRL 131 glass under the same test conditions after longer reaction times [62]. Analysis of samples reacted for shorter time periods showed the layer to evolve from a single clay phase to complex layer containing several distinct phases.…”
Section: Effects Of San On Alteration Layerssupporting
confidence: 72%
“…However, the thinness of the layers formed at 50 and 100 n-I may have prevented resolution of similar sublayers. The alteration phases observed on the sample reacted for 100 days at 10 rn-1 are consistent with those formed on SRL 131 glass under the same test conditions after longer reaction times [62]. Analysis of samples reacted for shorter time periods showed the layer to evolve from a single clay phase to complex layer containing several distinct phases.…”
Section: Effects Of San On Alteration Layerssupporting
confidence: 72%
“…Recently, Murakami et al (1989) and Copyright 9 1992, The Clay Minerals Society Banba et al (1990) examined the experimental alteration of synthetic borosilicate glass and observed both that an amorphous fibrous phase was initially produced within a "mottled phase" and that crystalline materials such as nontronite, chlorite, septechlorite, and/or stilpnomelane appeared to precipitate. Abrajano et al (1990) also reported secondary phyllosilicates precipitated from the leachant solution during simulated weathering of nuclear waste glasses. Tazaki et al (1989) observed the domain structure of crystalline regions within the noncrystalline volcanic glass matrix and the formation of clays with 14 and 16.7 ]k spacings and suggested that the crystalline regions represented noncrystalline matrix directly transformed into clay minerals.…”
Section: Introductionmentioning
confidence: 89%
“…In some open-system glass dissolution tests, the gel layer appears to serve as a transport barrier that limits the overall dissolution rate [13]. However, in most closed-system experiments, elemental release data and electron microscopic examination of the surface layers show that the overall reaction rate is not controlled by diffusion of elements through the alteration layers [14][15][16][17]. Note, however, that some recent Product Consistency Test (PCT) data [17] show a significant effect of surface layer formation and possible diffusional rate control for some simple borosilicate glass compositions.…”
Section: Overview Of Glass Dissolution Processesmentioning
confidence: 99%